Your Safety Net / Exploring the Issues of Safe Learning on the Internet (ATL - The Education Union, 2002)
The purpose of this booklet is to explore how the Internet can be effectively and safety used to aid Teaching and Learning. Introducing the Internet, Using the Internet in Your Teaching, Internet Safety, What are the Risks?, How Schools and Colleges Can Protect Students from the Risks, Using Technology, Using Education, Using Regulation, Adopting an Acceptable Use Policy, Looking to the Future, Further Information, Appendices.